A clinical study of primary caesarean section at a tertiary care hospital in coastal city: an observational study - T., Chaitanya K.; M., Lakshmi Manjeera (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean section represents the most significant operative intervention in obstetrics and its development and application has saved the lives of countless mothers and infants. However there has been a steady increase in the rate of caesarean sections worldwide. In this study, we aim to find the primary caesarean section rates and strategies to cut it down. Methods: This was a prospective observational study done from January 2018 to June 2019 at Justice K. S. Hegde Charitable Hospital, Deralakatte, Mangaluru which included 379 cases of primary cesarean sections. All patients undergoing primary caesarean section with gestational age >28 weeks confirmed by dates, clinical examination and ultrasound were included in this study. Patients who had undergone previous caesarean section or were less than 18 years of age or were less than 28 weeks of gestation were excluded from the study. Results: In this study the rate of primary caesarean section was found to be 14.5% and the majority of the study subjects belonged to the age group of 18-27 years (62.3%). With respect to parity, primigravida were high in number (71.2%), followed by multigravida. The number of emergency caesarean sections were (79%) more than elective (21%). The most common intra-operative complication was post-partum haemorrhage (PPH) in 2.8% and the most common postoperative complication was wound gape in 2.1%. Conclusions: Maximum efforts should be made to allow progression of vaginal delivery in primigravida which helps us to bring down the primary caesarean rate.